A housing development program in Brazilian slums : the social impact of TETO - Bueno, Leonardo da Rocha Loures (2021)
Lack of access to proper housing infrastructure is a problem affecting thousands of households in Brazil. Poor housing quality can be a source of unwanted consequences that may prevent the overcoming of poverty. The present dissertation explores a few outcomes that can originate from inadequate housing, but that are not commonly tackled in the design of policies. In partnership with the NGO TETO Brazil, I conducted a randomized controlled trial to evaluate the extent to which the organization’s housing program alleviates the subjective mental well-being and preventive behavior measures against COVID-19 of benefited families. The results support the claim that TETO’s intervention increases mental well-being in the short run but has null effects on behavioral measures in the fight against COVID-19. Additional findings highlight the importance of the social components of TETO’s housing program to explain these results. TETO improves pro-social behavior among participants of the program. For example, TETO has increased norms of trust and reciprocity, as well as networks and social ties.